Developing and Validating a Model of Tourism Brand Equity - Dahiya, Annu; Kumar, Rajiv; Sangeeta (Atna Journal of Tourism Studies, 2022)
Advertising and advertising media is a huge industry that stimulates all other industries whether it is in the primary, secondary or tertiary sector. Advertising plays a very important role in the service sector as it gives to tangibles the attribute of service that will create positive attitude towards service and decrease the perceived risk concerned with promoting tourism through advertising. Ministry of India launches many campaigns to make India a strong brand in tourism. A huge budget is kept aside for promoting Indian tourism at domestic as well as in the international level. Whenever money is invested, its result becomes too crucial to measure for two reasons- first the effect of invested money and second, money works as magnet for more money and so how effectively this money performs this magnetic function also becomes important. There are a number of measures to evaluate the above said performance but this paper focuses on the specific measure of advertising that is called communication effect or also known as brand equity. Here a scale is designed and validated for measuring the communication effect of advertising and it is done with the help of first and second order confirmatory factor analysis. The result shows that a good model with some modifications in the proposed model was developed and validated that consists of five dimensions and forty-four items after removing two items from the proposed model. This scale has been validated to measure the brand equity of tourism as a brand. This model has a good model fit and fulfill all reliability and validity conditions.